Pengaruh Tekanan Sosial Berupa Efek Hawthorne yang Menimbulkan Emosi Bangga atau Malu terhadap Perilaku Memilih Warga Jakarta Pusat pada Pemilu Legislatif 2014 (Jurnal Ilmiah Psikologi MIND SET, 2019)
Decreasing voter turnout urge non-partisan institutions or candidates to increase voter participation in election. One of the methods is get-out-the-vote by giving mail to the voters. Gerber, Green, and Larimer (2008) show that social pressure in the form of Hawthorne effects increases voter turnout.  When voters are observed, they are exerted to comply with social norms to get praise or to avoid chastisement. Moreover, emotions, such as pride and shame, also play role in the effect of social pressure on voting behavior. Panagopoulos (2010) shows that shame and pride increase voter turnout, and shame is more effective to increase voter turnout than pride. Using field experiment, researcher randomized 135 participants into three treatment groups: "Hawthorne" mailing, "Hawthorne with pride" mailing, and "Hawthorne with shame" mailing. The result was that social pressure in the form of Hawthorne effect decrease voting behavior. There was no difference among the treatment groups. Besides the inadequacy of the experiment, researchers also presume lack of voters' civil attitude as the cause of decreasing on voter turnout.